Strategi Komunikasi Pemerintah Kota Padang Dalam Meminimalisir Infodemic Vaksinasi Covid-19 - Rahmadhona Fitri Helmi; Pratiwi Nurhabibie; Yuliarti Yuliarti; Yulia Hanoselina (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2021)
Currently, the dissemination of information looks pretty excessive in the pandemic Covid-19; it is called an infodemic. As stated by WHO Director-General Tedros Adhanom Ghebreyesus, "…infodemic…spreads faster and more easily than virus Covid-19". Infodemic is information overload and cannot be traced to the truth, especially those circulating and developing during a health emergency. The percentage of vaccination refusal in Padang is relatively high, namely 11,2%, compared to the national rate, which is 5,2%. This requires the Government's communication strategy to provide valid information so that people are willing to be vaccinated. The study aims to analyze the communication strategy carried out by Padang Government in minimizing the Covid-19 vaccine infodemic. This study used a descriptive method with a qualitative approach—informants were withdrawn by purposive sampling. Collects data using observation techniques, interviews, and documentation studies. The results reveal that Padang Government's communication strategy in handling the Covid-19 vaccine infodemic is quite complete, clear, concise, and accurate. However, the substance of the information submitted has not conveyed in detail the safety and halalness of the Covid-19 vaccine. The Padang Government should involve the MUI of West Sumatra in answering public doubts about the Covid-19 vaccine